Intersections of identity and status in international students' perceptions of culturally engaging campus environments. (July 2022) - Glass, Chris R.; Heng, Tang T.; Hou, Minghui
Abstract: Higher education institutions have been criticised as neo-colonial entities that subjugate, other or silence international students. With a goal towards creating a more equitable and inclusive campus environment, this study aims to center the voices of international students and illuminate the heterogeneity of their perceptions of the campus environment. To this end, we investigated differences in 1681 international students' perceptions of culturally engaging campus environments by intersections of identity and status. Multivariate analysis of variance (MANOVA) examined identity variables (age, race, region, social class, first generation, and disability) and status variables (degree level, field of study, living situation, and visa status) on perceptions of culturally engaging campus environments. Findings indicate that region, visa status, and social class had a significant relationship with perceptions of cultural relevance and responsiveness. The results indicate two-way interactions between living situations and gender identification, as well as degree level and race. The discussion explores the need to understand the intersectional voices of students facing multiple discriminations to begin to equalize power differentials embedded within the neo-colonial relationship between higher education institutions and international students.